2018
DOI: 10.1007/s00261-018-1732-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acoustic radiation force impulse (ARFI) elastography as non-invasive diagnostic tool in living donor liver transplantation

Abstract: ARFI can be used as a reliable method in assessment of significant fibrosis post-LDLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…After exclusion of the studies by title/abstract and other publication types, 89 studies were carefully assessed for eligibility. Then, the studies concentrating on viral hepatitis, animal models and those without sufficient data were excluded, and a total of 29 studies were included for further analysis [9, (Fig 1). Among them, two studies concentrated on ARFI on biliary atresia-related hepatic fibrosis, two studies reported ARFI in diagnosing fibrosis caused by cystic fibrosis-associated liver disease.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…After exclusion of the studies by title/abstract and other publication types, 89 studies were carefully assessed for eligibility. Then, the studies concentrating on viral hepatitis, animal models and those without sufficient data were excluded, and a total of 29 studies were included for further analysis [9, (Fig 1). Among them, two studies concentrated on ARFI on biliary atresia-related hepatic fibrosis, two studies reported ARFI in diagnosing fibrosis caused by cystic fibrosis-associated liver disease.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…For instance, only 1/50000 of the whole liver tissue is sampled during a liver biopsy, for which sampling error is of concern [8]. The length of the specimens or the choice of the biopsy location might affect the accuracy of the results [9]. Moreover, repeated biopsies are infeasible in clinical settings for the sake of continuous monitoring of fibrosis grade [10].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other studies, the sample size for ARFI ( n = 69) was quite large (Abdelhaleem et al 2018: n = 70; Liao et al 2014: n = 57, Schmillevitch et al 2016: n = 33) ( 4 , 5 , 21 , 22 ). The cut-off at 1.29 m/s was more within the lower range of most other studies on ARFI in OLT recipients dominated by HCV reinfection, in which cut-off values ranged between 1.29 m/s and 1.75 m/s ( 4 , 23 25 ).…”
Section: Discussionmentioning
confidence: 80%
“…Through this, shear waves are propagated and their velocity can be measured in a certain region of interest. Results are described in m/s ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…124 In addition to its practical use in the clinic, studies have shown that ARFI performs comparably to TE and is applicable to both adult and pediatric populations. [125][126][127][128][129][130][131][132][133] Meanwhile, SWE quantifies stiffness similarly to TE with the advantage of measuring liver stiffness in several regions of interest in real time. 134 However, SWE tends to have lower performance metrics compared with ARFI and TE in LT recipients; thus, its use may be limited in the clinic.…”
Section: Imaging Modalitiesmentioning
confidence: 99%